Development and Validation of a Nomogram to Predict Lymph Node Metastasis in Patients With T1 High-Grade Urothelial Carcinoma of the Bladder - Ou, Ningjing; Song, Yuxuan; Liu, Mohan; Zhu, Jun; Yang, Yongjiao; Liu, Xiaoqiang (Frontiers in Oncology, 2020)
Purpose This study aims to develop and validate a nomogram to predict lymph node metastasis preoperatively in patients with T1 high grade urothelial carcinoma. methods We retrospectively evaluated the data of 2689 patients treated with RC and bilateral lymphadenectomy at UCB in two medical centers. Eventually, 412 patients with T1 high grade urothelial carcinoma were enrolled in the primary cohort to develop a prognostic nomogram designed to predict lymph node status. An independent validation cohort (contained 783 consecutive patients during the same period) was subjected to validate the predicting model. Binary regression analysis was used to develop the predicting nomogram. We assessed the performance of the nomogram concerning its clinical usefulness, calibration, and discrimination. Results Overall, 69(16.75%) and 135 (17.24%) patients had lymph node metastasis in the primary cohort and external validation cohort. The final nomogram included information on tumour number, tumour size, lymphovascular invasion, fibrinogen, and MLR. The nomogram showed good predictive accuracy and calibration with concordance index in the primary cohort of 0.853. Application of the nomogram in the external validation cohort still gave good discrimination (C-index, 0.845) and good calibration. The analysis of the decision curve shows that the nomogram has clinical application value. Conclusions The nomogram that incorporated the tumour number, tumour size, lymphovascular invasion, fibrinogen, and MLR showed favourable predictive accuracy for lymph node metastasis. It may be conveniently used to predict lymph node metastasis in patients with T1 high grade Urothelial Carcinoma and be helpful in guiding treatment decisions.